Analysis of Pulsed wire measurements on bi-harmonic undulator. (March 2016) - Sharma, Geetanjali; Mishra, G.; Gehlot, Mona
Highlights: A pulsed wire system is tested for bi-harmonic undulator field measurements. The pulsed wire data for field integral is compared with Hall probe data. Two different detection systems and two wires of different diameters are used. Pulsed wire data gives comparable results as Hall probe data for both the wire dia. The results proves ability of PWM to measure multi peak magnetic field profile. Abstract: In this paper we report measurement of bi-harmonic undulator in a Pulsed wire bench. The pulsed wire data for field integral is compared with Hall probe data. It is observed that the wire rigidity and stiffness of the thick wire do not affect the bi harmonic undulator field measurement and gives comparable results with Hall probe data.